Defining habitat demands of Wels catfish (Silurus glanis) in a Swedish lake - Spange, David (2018)
The wels catfish (Silurus glanis) is a rare species in Swedish waters, it demands higher water temperatures than most lakes and rivers can offer. One of the few locations with naturally occurring wels catfish in Sweden is Lake Båven, situated about an hour and a half south of Stockholm, in the county of Södermanland. Due to declines of the Swedish catfish populations, which are mostly a result of human impacts such as the destruction of spawning habitats, conservational actions are now needed in purpose to secure the future of the species in Sweden.